A novel role of the mitochondrial permeability transition pore in (−)-gossypol-induced mitochondrial dysfunction. (March 2018) - Warnsmann, Verena; Meyer, Nina; Hamann, Andrea; Kögel, Donat; Osiewacz, Heinz D.
Highlights: Gossypol-induces oxidative stress, mitochondrial dysfunction and autophagy. Gossypol treatment induces cell death in globlastoma cells. Gossypol treatment decreases lifespan in Podospora anserina . The effects of gossypol require opening of the mitochondrial transition pore. Abstract: Gossypol, a natural polyphenolic compound from cotton seeds, is known to trigger different forms of cell death in various types of cancer. Gossypol acts as a Bcl-2 inhibitor that induces apoptosis in apoptosis-competent cells. In apoptosis-resistant cancers such as glioblastoma, it triggers a non-apoptotic type of cell death associated with increased oxidative stress, mitochondrial depolarisation and fragmentation. In order to investigate the impact of gossypol on mitochondrial function, the mitochondrial permeability transition pore and on oxidative stress in more detail, we used the aging model Podospora anserina that lacks endogenous Bcl-2 proteins. We found that treatment with gossypol selectively increases hydrogen peroxide levels and impairs mitochondrial respiration in P. anserina, apoptosis-deficient Bax/Bak double knockout mouse embryonal fibroblasts and glioblastoma cells. Significantly, we provide evidence that CYPD-mediated opening of the mPTP is required for gossypol-induced mitochondrial dysfunction, autophagy and cell death during organismic aging of P. anserina and in glioblastoma cells. Overall, these data provide new insights into the role of the mPTP and autophagy in the antitumor effects of gossypol, a natural compound that is clinically developed for the treatment of cancer.